PELVIC ORGAN PROLAPES - Mira Pratiwi, Ketut Yoga; Mega Putra, I Gede (E-Jurnal Medika Udayana, 2013)
Pelvic organ prolapse (POP) is defined as a decrease in abnormal or herniation of the pelvic organs out of place attached to its normal position or in the pelvic cavity. As for the anatomy of the pelvic organs consists of bones, muscles, and nerves. The presence of damage to the pelvic connective tissue and visceral attachment pelvic organs the cause occurs. The symptoms that appear in patients POP not specific to distinguish prolapse of some compartments but can reflect the degree of prolapse as a whole. Physical examination focused on pelvic examination, beginning with inspection on the vulva and vagina to identify the presence of erosion, ulceration, or other lesions. As for the existing therapy options include observation, non-operative management, and operative management.
Keywords: Pelvic organ prolapse, Anatomy, symptoms, physical examination, management